STEM Graduates, Human Capital Externalities, and Wages in the U.S. - John V. Winters (Institute for the Study of Labor (IZA), 2013)
Previous research suggests that the local stock of human capital creates positive externalities within local labor markets and plays an important role in regional economic development. However, there is still considerable uncertainty over what types of human capital are most important. Both national and local policymakers in the U.S. have called for efforts to increase the stock of college graduates in science, technology, engineering, and mathematics (STEM) fields, but data availability has thus far prevented researchers from directly connecting STEM education to human capital externalities. This paper uses the 2009-2011 American Community Survey to examine the external effects of college graduates in STEM and non-STEM fields on the wages of other workers in the same metropolitan area. I find that both types of college graduates create positive wage externalities, but STEM graduates create much larger externalities.
Keywords: J24; R23; 330; human capital externalities; STEM; wage growth; agglomeration